2016
DOI: 10.1007/s00277-016-2806-8
|View full text |Cite
|
Sign up to set email alerts
|

How can we help haematological cancer survivors cope with the changes they experience as a result of their cancer?

Abstract: Haematological cancer often necessitates that individuals make significant lifestyle and behaviour changes to protect themselves against infections. It is essential that haematological cancer survivors receive the support and information they require to adjust to such changes. This cross-sectional survey of 259 haematological cancer survivors found that over two thirds of haematological cancer survivors would like to receive more detailed information or help with: diet and nutrition that takes into account the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Several studies have been conducted to assess the differences between HASS and CASS, but the study on Chinese children is limited. Regarding the difference in basic diseases, published data have suggested that most blood malignancies in HASS patients can lead to immune deficiency, which is a risk factor for infection and death [19][20][21]. In addition, neutropenia was shown to be one of the factors that could increase the risk of infection [22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to assess the differences between HASS and CASS, but the study on Chinese children is limited. Regarding the difference in basic diseases, published data have suggested that most blood malignancies in HASS patients can lead to immune deficiency, which is a risk factor for infection and death [19][20][21]. In addition, neutropenia was shown to be one of the factors that could increase the risk of infection [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies state that patients with HASS were mainly older children with underlying diseases (76.9%); whereas, 65.9% patients had hematologic/oncologic diseases. Research also suggests that most of the blood malignancies in HASS patients can lead to immune de ciency, which is a risk factor for infection and death [15][16][17]. Compared with CASS, children with HASS had signi cantly lower WBCs and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…A need for information regarding side effects and how to manage them was identified in eight studies, 22,[28][29][30][31][32][33][34] seven of which provide some evidence that this need was unmet for many rural cancer survivors. 22,[29][30][31][32][33][34] For example, survey results showed that 11%-47% of rural survivors reported not receiving information on managing the side effects of treatment.…”
Section: Managing Side Effects and Self-managementmentioning
confidence: 99%